2009
DOI: 10.1016/j.neuron.2008.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Modulation of Sleep Homeostasis and Cognitive Consequences of Sleep Loss

Abstract: Astrocytes modulate neuronal activity by releasing chemical transmitters via a process termed gliotransmission. The role of this process in the control of behavior is unknown. Since one outcome of SNARE-dependent gliotransmission is the regulation of extracellular adenosine and because adenosine promotes sleep, we genetically inhibited the release of gliotransmitters and asked if astrocytes play an unsuspected role in sleep regulation. Inhibiting gliotransmission attenuated the accumulation of sleep pressure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
715
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 772 publications
(769 citation statements)
references
References 27 publications
32
715
2
5
Order By: Relevance
“…Recent evidence strongly suggests a role for extracellular adenosine as an endogenous somnogen. 53,57,[60][61][62][63][64] ATP can act as a somnogen not only through its conversion to adenosine but also through the binding of extracellular ATP to P2-type transmembrane receptors, a step that leads to the release, largely from microglial cells (brain phagocytes), of cytokines that include interleukin-1b (IL1b) and tumor necrosis factor (TNF)-a. 56,65,66 As described below, these and other inflammatory cytokines can act as somnogens, indicating a major but incompletely understood connection between the immune system and sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence strongly suggests a role for extracellular adenosine as an endogenous somnogen. 53,57,[60][61][62][63][64] ATP can act as a somnogen not only through its conversion to adenosine but also through the binding of extracellular ATP to P2-type transmembrane receptors, a step that leads to the release, largely from microglial cells (brain phagocytes), of cytokines that include interleukin-1b (IL1b) and tumor necrosis factor (TNF)-a. 56,65,66 As described below, these and other inflammatory cytokines can act as somnogens, indicating a major but incompletely understood connection between the immune system and sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the early studies of gliotransmission, the concept of the tripartite synapse was proposed[94], highlighting the role of the astrocyte as a third active element in information processing at the synapse[95,96,97,98,99]. Although many aspects of this astrocytes-to-neuron communication are still to be elucidated[89,100] (for reviews, see [101,102,103]), the introduction of molecular genetic tools[83] is shedding light on the neuromodulatory roles of astrocytes on brain function at the level of synapses[83], circuits[104], and behavior[105]. …”
Section: Astrocytes As Neuromodulatorsmentioning
confidence: 99%
“…By studying the natural sleep behavior of dnSNARE mice with chronic EEG recordings, we observed that these animals show impaired accumulation of slow wave activity (SWA) as a function of prior wakefulness[105]. This deficit is present both under baseline conditions (while animals are undisturbed in their cages) and following sleep deprivation by gentle handling.…”
Section: Slow Oscillations As a Manifesation Of Integrated Brain Circmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical dynamics within this space are hypothesized to play key roles in cancer, spreading depression, epilepsy and sleep disorders. (3)(4)(5)(6) The purpose of this essay is to consider what we can learn from this space and the methods for following the dynamics of chemical movement within the diffusive boundary layers that comprise an integral part of a cell. We will start by noting the physical and chemical features involved.…”
mentioning
confidence: 99%